Development and validation of a reliable reverse-phase high-performance liquid chromatography method for quantifying triterpenes in Centella asiatica: A step towards quality control of herbal products - Suwanpitak, Kittipat; Sangnim, Tanikan; Sriamornsak, Pornsak; Puri, Vivek; Sharma, Ameya; Huanbutta, Kampanart (Science, Engineering and Health Studies, 2025)
Centella asiatica (C. asiatica), a medicinal plant with diverse pharmacological properties, contains triterpenes with pharmaceutical activity, including madecassoside (MC), asiaticoside (AC), madecassic acid (MA), and asiatic acid (AA). However, the current assay for these triterpenes in the United States Pharmacopeia 36–National Formulary 31 could be enhanced with improved compound separation and shorter analysis times. A new reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated, which utilized a C18 column with low-pressure gradient elution and a rapidly altered mobile phase ratio (acetonitrile and 0.3% v/v phosphoric acid in water). This method offered significantly reduced analysis times and suitable peak shapes for all triterpenes. The retention times were 11.49, 11.84, 14.67, and 15.74 min for MC, AC, MA, and AA, respectively. The method displayed linearity (R² > 0.9907) across a 0.01–0.25 mg/mL range, and its accuracy was confirmed by spiked sample recoveries of 90.60%–111.50%. The repeatability and intermediate precision were outstanding, with percentage of relative standard deviations lower than 1.31% for all triterpenes. This validated RP-HPLC method offers an accurate and time-saving alternative for analyzing C. asiatica triterpenes, providing a practical solution for the pharma-ceutical and herbal product industries.